High-performance data network design : design techniques and tools - Kenyon, Tony, 1960- (Digital Press, 2002)
High-Performance Data Network Design contains comprehensive coverage of network design, performance, and availability. Tony Kenyon provides the tools to solve medium- to large-scale data network design problems from the ground up. He lays out a practical and systematic approach that integrates network planning, research, design, and deployment, using state-of-the-art techniques in performance analysis, cost analysis, simulation, and topology modeling. The proliferation and complexity of data networks today is challenging our ability to design and manage them effectively. A new generation of Internet, e-commerce, and multimedia applications has changed traditional assumptions on traffic dynamics, and demands tight quality of service and security guarantees. These issues, combined with the economics of moving large traffic volumes across international backbones, mean that the demands placed on network designers, planners, and managers are now greater than ever before. High-Performance Data Network Design is a "must have" for anyone seriously involved in designing data networks. Together with the companion volume, Data Networks: Routing, Security, and Performance Optimization, this book gives readers the guidance they need to plan, implement, and optimize their enterprise infrastructure. Provides real insight into the entire design process Includes basic principles, practical advice, and examples of design for industrial-strength enterprise data networks Integrates topics often overlookedbackbone optimization, bottleneck analysis, simulation tools, and network costing